11.1k views
4 votes
If f(x)=3x-1 and g(x)=x+5, find (f o g)(x) and (g o f)(x)

(f o g)(x)=

(g o f)(x)

User PhilMY
by
5.0k points

2 Answers

9 votes

Answer:

(f o g)(x)= 3x + 14

(g o f)(x) = 3x + 4

Explanation:

(f o g)(x) = f(g(x)) = f(x + 5) = 3(x + 5) - 1 = 3x + 15 - 1 = 3x + 14

(g o f)(x) = g(f(x)) = g(3x - 1) = 3x - 1 + 5 = 3x + 4

User Logan Fuller
by
4.7k points
5 votes

Answer:


(f \circ g)(x) = 3x + 14


(g \circ f)(x) = 3x + 4

Explanation:

Hello!

Rewrite the equations:


  • (f \circ g)(x) = f(g(x))

  • (g \circ f)(x) = g(f(x))

Given that:

  • f(x) = 3x - 1
  • g(x) = x + 5

Solve for
(f \circ g)(x):


  • f(g(x)) = 3(g(x)) - 1

  • f(x + 5) = 3(x + 5) - 1

  • f(x + 5) = 3x + 15 - 1

  • f(x + 5) = 3x + 14


(f \circ g)(x) = 3x + 14

Solve for
(g \circ f)(x):


  • g(f(x)) = f(x) + 5

  • g(3x - 1) = (3x - 1) + 5

  • g(3x - 1) = 3x +4


(g \circ f)(x) = 3x + 4

User Trake Vital
by
5.0k points